Tongue–palatal contact changes in patients with skeletal mandibular prognathism after sagittal split ramus osteotomy: an electropalatography study. (24th June 2017) - Kojima, S.; Kaku, M.; Yamamoto, I.; Yasuhara, Y.; Sumi, H.; Yamamoto, T.; Yashima, Y.; Izumino, J.; Nakajima, K.; Nagano, Y.; Kono, M.; Yoshimura, A.; et al.
Summary: The purpose of this study was to investigate the changes in tongue–palatal contact patterns using electropalatography (EPG) before and after sagittal split ramus osteotomy (SSRO) in patients with mandibular prognathism. Nine clients who underwent SSRO for mandibular setback and seven control subjects were participated in this study. Tongue–palatal contact patterns for /t/, /s/ and /k/ production were investigated using EPG before surgery and 3 months after surgery. The mean value of whole total of palate contact (WT) in the maximum contact frame was examined before and after SSRO. The correlation quantity between the change of center of gravity (COG) value and the amount of mandibular setback was also evaluated. The mean value of WT for /t/ and /s/ significantly increased after SSRO, and the EPG pattern became normal. However, a remarkable change in WT for /k/ was not observed, and the mean value was significantly larger in the SSRO group before and after surgery than in the control group. A negative correlation between COG variation and the amount of mandibular setback for /t/ and positive correlation for /s/ was observed. This study demonstrated that tongue–palatal contact patterns for /t/ and /s/ articulation improved clearly after SSRO. There was a significant correlation between COG variation and the amount of mandibular setback. However, no significant change was detected through perceptual assessment before and after SSRO. Further investigation is needed to determine whether these results will change over time.